2021
DOI: 10.3390/su13126824
|View full text |Cite
|
Sign up to set email alerts
|

The Nexus between Sustainable Economic Development and Government Health Expenditure in Asian Countries Based on Ecological Footprint Consumption

Abstract: Health has vital importance in maintaining economic development since it is essential for, and a result of, economic development. This indicates that health makes a large contribution in achieving sustainable development and health outcomes. The significance of health is shown in the millennium development goals (MDGs) and in the sustainable development goals (SDGs), where four of the seventeen objectives focus on improving health outcomes (UN, 2021). As compared to other countries, some Asian countries are st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…In order to investigate causality between economic development and healthcare expenditure, scientists used numerical econometric instruments (ARDL, GMM, OLS regression, Granger causality test, panel-type VECM model, etc. ), but in the paper, a unified econometric instrument is proposed—panel data GLS regression and Hausman test as is also proposed in [ 17 ]. So, the panel data regression modelling toolkit will be used to fulfil this task.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to investigate causality between economic development and healthcare expenditure, scientists used numerical econometric instruments (ARDL, GMM, OLS regression, Granger causality test, panel-type VECM model, etc. ), but in the paper, a unified econometric instrument is proposed—panel data GLS regression and Hausman test as is also proposed in [ 17 ]. So, the panel data regression modelling toolkit will be used to fulfil this task.…”
Section: Methodsmentioning
confidence: 99%
“…While most of the research mentioned above considered economic growth and sustainability within the traditional growth model approach, in the papers [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], a country’s economic development is characterised through a complex and systemic approach using the following indicators: central government debt, total % of GDP; GDP growth, annual %; GDP per capita, PPP constant 2011 international USD; gross fixed capital formation, % of GDP; income share held by the lowest 20%; industry value added, annual % growth; research and development expenditure, % of GDP; unemployment, % of the total labour force; current account balance, % of GDP [ 17 , 18 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Ghasemi et al (2021) revealed that sustainable criteria cover all economic, social, and environmental dimensions. Moreover, Qaiser Gillani et al (2021) highlighted the fact that a healthy environment results in healthy people and sustainable development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a macro-level strand, health, education, and employment are the essential components of nurturing the human capital of a nation to bring welfare and prosperity, yet they have been proven to be vulnerable sectors that have received substantial assaults during wartime [ 2 , 3 ]. Moreover, health spendings mainly aim to result in the efficient provision of health prospects, strengthening human capital to improve overall productivity, thus contributing to welfare and efficient economic performance [ 4 ]. It is therefore important to understand the pattern of healthcare spending in a conflict zone during wartime.…”
Section: Introductionmentioning
confidence: 99%